Substance Use-Associated Mortality among Heart Donors after the COVID-19 National Emergency Increased but Did Not Affect Peri-Transplant Outcomes - Meg Fraser; Bellony Nzemenoh; Scott Jackson; Thanat Chaikijurajai; Robert Halmosi; Kalman Toth; Wahab J. Khan; Tamas Alexy (Journal of Cardiovascular Development and Disease, 2023)
Introduction: The COVID-19 pandemic and consequent social isolation prompted a surge in mental health disorders and substance use in the general population and, therefore, in potential organ donors. We aimed to evaluate if this led to a change in donor characteristics, including the mechanism and circumstance of death, and how this may have affected clinical outcomes following heart transplantation. Methods: We identified all heart donors from the SRTR database between 18 October 2018 and 31 December 2021, excluding those who donated immediately after the US national emergency declaration. Donors were stratified into pre-COVID-19 (Pre-Cov; through 12 March 2020) and post-COVID-19 national emergency declaration cohorts (Post-Cov; 1 August 2020 through 31 December 2021) based on the heart procurement date. Relevant demographics, cause of death, and substance use history were collected in addition to graft cold ischemic time, the incidence of primary graft dysfunction (PGD), and recipient survival at 30 days post-transplant. Results: A total of 10,314 heart donors were identified; 4941 were stratified into the Pre-Cov and 5373 into the Post-Cov cohorts. There was no difference in demographics, but illicit drug use was significantly higher in the Post-Cov group, leading to an increased incidence of death from drug intoxication. Fatal gunshot wounds were also more common. Despite these changes, the incidence of PGD remained similar (p = 0.371), and there was no difference in 30 days recipient survival (p = 0.545). Conclusion: Our findings confirm that COVID-19 had a major impact on mental health and psychosocial life with an associated increase in illicit substance use and fatal intoxication rates in heart transplant donors. These changes did not alter peri-operative mortality following heart transplantation. Future studies are needed to ensure that long-term outcomes remain unaffected.